2022
DOI: 10.21203/rs.3.rs-1291395/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postoperative morbidity and health-related quality of life in children with delayed reconstruction of esophageal atresia: a nationwide Swedish study

Abstract: Background In 10-15% of children with esophageal atresia (EA) delayed reconstruction of esophageal atresia (DREA) is necessary due to long-gap EA and/or prematurity/low birth weight. They represent a patient subgroup with high risk of complications. We aimed to evaluate postoperative morbidity and health-related quality of life (HRQOL) in a Swedish national cohort of children with DREA. Methods Postoperative morbidity, age-specific generic HRQOL (PedsQLTM 4.0) and condition-specific HRQOL (The EA-QOL questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…In addition, no primary anastomosis, esophageal dilatation, as well as gastrostomy insertion secondary to long-gap EA or severe gastroesophageal reflux predicted worse scores related to eating domain in all ages; associated anomalies were related to worse body perceptions (16). Another research stated that days of discharge after EA repair and concomitant abnormalities were significantly negatively correlated with HRQOL scores in the 2-7 age group, while relevant respiratory and digestive tract symptoms such as airway infection, swallowing difficulties, and heartburn were associated with lower HRQOL scores in the 8-17 years group (28). Our results support the relevant opinions of the previous literature.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, no primary anastomosis, esophageal dilatation, as well as gastrostomy insertion secondary to long-gap EA or severe gastroesophageal reflux predicted worse scores related to eating domain in all ages; associated anomalies were related to worse body perceptions (16). Another research stated that days of discharge after EA repair and concomitant abnormalities were significantly negatively correlated with HRQOL scores in the 2-7 age group, while relevant respiratory and digestive tract symptoms such as airway infection, swallowing difficulties, and heartburn were associated with lower HRQOL scores in the 8-17 years group (28). Our results support the relevant opinions of the previous literature.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, a large multicentre study of management and outcomes of isolated LGOA treatment using DPA revealed a high rate of successful reconstructions, but prolonged LOHS (median 125 days) with a median age at repair of 87 days [23]. A long initial hospital stay, as well as significant associated anomalies, and persistent digestive or respiratory symptoms may negatively influence on health related quality of life (HRQOL) [24]. Other studies have also remarked that a prolonged hospital stay may be related to suboptimal long-term morbidity and neurodevelopment outcomes [25,26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%